The cycles of constitutional time - Balkin, J. M. (Jack Balkin, 2020)
America's constitutional system evolves through the interplay between three cycles: the rise and fall of dominant political parties, the waxing and waning of political polarization, and alternating episodes of constitutional rot and constitutional renewal. America's politics seems especially fraught today because we are nearing the end of the Republican Party's long political dominance, at the height of a long cycle of political polarization, and suffering from an advanced case of "constitutional rot." Constitutional rot is the historical process through which republics become increasingly less representative and less devoted to the common good. Caused by increasing economic inequality and loss of trust, constitutional rot seriously threatens the constitutional system. But America has been through these cycles before, and will get through them again. America is in a Second Gilded Age slowly moving toward a second Progressive Era, during which polarization will eventually recede. The same cycles shape the work of the federal courts and theories about constitutional interpretation. They explain why political parties have switched sides on judicial review not once but twice in the twentieth century. Polarization and constitutional rot alter the political supports for judicial review, make fights over judicial appointments especially bitter, and encourage constitutional hardball. The Constitution ordinarily relies on the judiciary to protect democracy and to prevent political corruption and self-entrenching behavior. But when constitutional rot is advanced, the Supreme Court is likely to be ineffective and may even make matters worse. Courts cannot save the country from constitutional rot; only political mobilization can"--